2003
DOI: 10.1002/nau.10086
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with voiding function in women with lower urinary tract symptoms: A mathematic model explanation

Abstract: Age, menopause, parity, and urethral mobility may change the hydrodynamics of the lower urinary tract and have varying impact on the voiding function by altering urethral distensibility. Moreover, poor detrusor power in the postmenopausal women may complicate the analysis of voiding function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…2 In addition, straining at voiding may be pathophysiological or represent a voiding habit that is not necessarily pathologic. 3,4 Studies in humans 2,4,5 have shown that in female subjects with lower urinary tract symptoms, straining at voiding is associated with urodynamic parameters that signify urethral obstruction. When the bladder is full voiding may be autonomous without the contribution of abdominal strain.…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition, straining at voiding may be pathophysiological or represent a voiding habit that is not necessarily pathologic. 3,4 Studies in humans 2,4,5 have shown that in female subjects with lower urinary tract symptoms, straining at voiding is associated with urodynamic parameters that signify urethral obstruction. When the bladder is full voiding may be autonomous without the contribution of abdominal strain.…”
Section: Introductionmentioning
confidence: 99%
“…This age bias is to be anticipated considering many abnormalities of the urinary tract are age-related, and in particular urethral function may be altered due to a decline in circulating estrogen after menopause. 13,14 Imaging had a high NPV but poor PPV, indicating that imaging may be useful in contributing to a decision not to perform cystoscopy if normal. Clinical risk factors were less helpful in determining who should have cystoscopy, but in the absence of risk factors and combined with normal imaging studies, no woman had an abnormal cystoscopy in this study.…”
mentioning
confidence: 99%
“…Abdominal muscle straining during voiding in humans is usually considered to be a symptom of bladder outflow obstruction [ 20 , 21 ]. However, clinical observations have failed to demonstrate a consistent relationship between abdominal straining and micturition in healthy subjects or in those with bladder outlet obstruction, suggesting the possibility of nonpathological muscle activity [ 4 , 22 , 23 ]. The maintenance of abdominal pressure has also been later proven to be an important factor in promoting vesical contraction in humans [ 24 ], as well as in animal investigations that confirmed the function of abdominal musculature in improving voiding efficiency [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%